The Translational Science Benefits Model, a new training tool for demonstrating implementation science impact: A pilot study - Stephanie Andersen; Annalee Wilson; Todd Combs; Laura Brossart; Julie Heidbreder; Stacey McCrary; Rinad S. Beidas; Leopoldo J. Cabassa; Erin P. Finley; Emma E. McGinty; Jonathan Purtle; Lisa Saldana; et al. (Journal of Clinical and Translational Science, 2024)
Abstract